2020
DOI: 10.1007/s43207-020-00036-x
|View full text |Cite
|
Sign up to set email alerts
|

Sweet ceramics: how saccharide-based compounds have changed colloidal processing of ceramic materials

Abstract: Herein, we present manifold possibilities of using saccharides and their derivatives in colloidal processing of ceramics. Sugar-based compounds are attractive alternatives for commonly used organic additives, because they are renewable materials, are non-toxic to human skin, and have a positive influence on the rheological behavior and stability of ceramic suspensions which is reflected in the properties of green and sintered bodies. The examined substances include sugar acids (galacturonic and lactobionic aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 73 publications
1
6
0
Order By: Relevance
“…This is evidenced by the occurrence of small hysteresis loops. Considering previous literature reports, [31,34,35] such a result was to be expected.…”
Section: A Analysis Of the Casting Slips' Rheological Propertiessupporting
confidence: 62%
“…This is evidenced by the occurrence of small hysteresis loops. Considering previous literature reports, [31,34,35] such a result was to be expected.…”
Section: A Analysis Of the Casting Slips' Rheological Propertiessupporting
confidence: 62%
“…4 wt.%) of monomers due to the formation method they chose—gelcasting. Moreover, it should be pointed out that thixotropic properties of aqueous ceramic suspensions may also be displayed when other modifiers are proposed, e.g., 6-O-acryloyl-d-galactose described in the work of Wiecinska et al [ 42 ], or metallic additives as reported earlier [ 22 ].…”
Section: Resultsmentioning
confidence: 99%
“…24 The sugar and polysaccharides present in AV mucilage provide a binding effect during the compaction of ceramic particles. 33 AV solution also helped in uniform mixing and homogeneous distribution of particles during the particle compaction process. For organic binders, glass transition temperature (T g ) plays an important role during the compaction of powder processing.…”
Section: Discussionmentioning
confidence: 99%